On the way back from 3D to 2D: Chitosan promotes adhesion and development of neuronal networks onto culture supports. (1st December 2022) - Di Lisa, Donatella; Muzzi, Lorenzo; Pepe, Sara; Dellacasa, Elena; Frega, Monica; Fassio, Anna; Martinoia, Sergio; Pastorino, Laura
Abstract: Most in vitro functional and morphological studies for developing nervous system have been performed using traditional monolayer cultures onto supports modified by extracellular matrix components or synthetic biopolymers. These biomolecules act as adhesion factors essential for neuronal growth and differentiation. In this study, the use of chitosan as adhesion factor was investigated. Primary rat neurons and neurons differentiated from human induced pluripotent stem cells were cultured onto chitosan and standard adhesion factors modified supports. The initiation, elongation and branching of neuritic processes, synaptogenesis and electrophysiological behavior were studied. The biopolymers affected neurites outgrowth in a time dependent manner; in particular, chitosan promoted neuronal polarity in both cell cultures. These results indicate chitosan as a valid adhesion factor alternative to the standard ones, with the advantage that it can be used both in 2D and 3D cultures, acting as a bridge between these in vitro models. Graphical abstract: Unlabelled Image